The European Project HIALINE: Three Years of Monitoring Pollen and Allergens of Betula in Parma (Italy) - Albertini, Roberto (2012)
The results in Italy should be compared with those from partners in other counlries. II will be important to confirm some observations during the first and second year of the projecl activity which showed the presence of a different allergenic power in difleren! geographical areas as observed for other types of pollen (Poaceae and Olea). The aim of lhe project was to measure the pollen's capacity to release allergens and this will result inlo an allergen exposure forecast, taking into consideration pollen counts and allergen release trom diflerent locations. The results of the project will help medical doctors, authorities and patients to better manage lhe diflerent aspects related to pollinosis.